On the Oscillation of Second-Order Neutral Delay Differential Equations - Han Zhenlai; Li Tongxing; Sun Shurong; Chen Weisong (Advances in Difference Equations, 2010)
Some new oscillation criteria for the second-order neutral delay differential equation , are established, where , , , . These oscillation criteria extend and improve some known results. An example is considered to illustrate the main results.